PENGARUH PROFITABILITAS, LIKUIDITAS, SOLVABILITAS, DAN PERTUMBUHAN PERUSAHAAN TERHADAP OPINI AUDIT GOING CONCERN PADA PERUSAHAAN SEKTOR BARANG KONSUMEN NON-PRIMER YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2021 - Khamsiyahni, Rizqi Anandita; Amin, Muhammad Nuryatno (Politeknik Negeri Ambon, 2023)
This study aims to examine the influence of profitability, liquidity, solvability, and company growth on going concern audit opinion in consumer cyclicals companies that have been listed on the Indonesia Stock Exchange (BEI) for the 2019-2021 period. This type of this study was causal comparative research. The population in this study is Consumer Cyclicals Company that listed in Indonesian Stock Exchange on 2019-2021. Sampling technique that used in this study was purposive sampling. The number of samples used in this study was 51 companies from total 124 consumer cyclicals companies that listed in Indonesia Stock Exchange on 2019-2021, so the research data analyzed amounted to 153. The data were analyzed by using descriptive statistic and logistic regression analysis. Research data is processed using SPSS software. The results of this study showed that profitability and liquidity have a significant negative effect on going concern audit opinion, while solvability and company growth have no effect on going concern audit opinion.